2007
DOI: 10.1038/sj.emboj.7601902
|View full text |Cite
|
Sign up to set email alerts
|

ACF catalyses chromatosome movements in chromatin fibres

Abstract: Nucleosome-remodelling factors containing the ATPase ISWI, such as ACF, render DNA in chromatin accessible by promoting the sliding of histone octamers. Although the ATP-dependent repositioning of mononucleosomes is readily observable in vitro, it is unclear to which extent nucleosomes can be moved in physiological chromatin, where neighbouring nucleosomes, linker histones and the folding of the nucleosomal array restrict mobility. We assembled arrays consisting of 12 nucleosomes or 12 chromatosomes (nucleosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 69 publications
5
45
0
Order By: Relevance
“…ACF consists only of ISWI and ACF1, whereas CHRAC additionally contains two small histone-fold subunits (Eberharter et al, 2001;Ito et al, 1997). In vitro, ACF can promote the assembly of regular arrays of nucleosomes or chromatosomes (Lusser et al, 2005), and can catalyse the movement of nucleosomes and chromatosomes in arrays (Eberharter et al, 2004;Maier et al, 2008). Biochemically, CHRAC and ACF have very similar properties (Hartlepp et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…ACF consists only of ISWI and ACF1, whereas CHRAC additionally contains two small histone-fold subunits (Eberharter et al, 2001;Ito et al, 1997). In vitro, ACF can promote the assembly of regular arrays of nucleosomes or chromatosomes (Lusser et al, 2005), and can catalyse the movement of nucleosomes and chromatosomes in arrays (Eberharter et al, 2004;Maier et al, 2008). Biochemically, CHRAC and ACF have very similar properties (Hartlepp et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We found that ACF or its ATPase ISWI alone were able to significantly increase the access to DNA packaged in these arrays, even if they were saturated with linker histones H1 or H5 (Maier et al, 2007). Moreover, ACF catalyzed the repositioning of entire chromatosomes within these arrays (Figure 1d,g).…”
Section: Atp-dependent Remodeling Of H1-containing Chromatinmentioning
confidence: 79%
“…In our assay, linker histones almost entirely inhibited the remodeling activity of CHD1, whereas ACF remained surprisingly active (Maier et al, 2007). Because the presence of H1 affects both chromatin assembly and remodeling activities of these enzymes in similar ways, the two processes might be mechanistically linked.…”
Section: Atp-dependent Remodeling Of H1-containing Chromatinmentioning
confidence: 84%
See 1 more Smart Citation
“…Nucleosome remodelling factors differ in their ability to remodel nucleosomes in the presence of the linker histone. Those machineries, such as the ISWI-containing ACF complex (Maier et al, 2008b), that are able to move nucleosomes together with associated H1 may be better called 'chromatin remodelling factors' (reviewed in Maier et al, 2008a). In this study we discuss how chromatin remodelling factors can affect the incorporation of linker histones during development, again using the Drosophila paradigm as an example.…”
Section: Linker Histones: Links Between Nucleosomes Chromatin Fibre Fmentioning
confidence: 99%